Structural study of enteroviruses - Qin, L (2023)
Enteroviruses comprise a genus of picornaviruses causing global morbidity and regional outbreaks. These viruses are the causative agents of severe, widespread diseases such as hand-foot-and-mouth disease, poliomyelitis and aseptic meningitis. Although they have been studied for decades, few vaccines or drugs are in use. Indeed, many structural details of enterovirus infection, immune response and life cycle remain unknown. Solving these structural mysteries may provide crucial information that aids the elimination of these infectious particles.